2000
DOI: 10.1054/bjoc.1999.0883
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale UK audit of blood transfusion requirements and anaemia in patients receiving cytotoxic chemotherapy

Abstract: Cancer patients receiving cytotoxic chemotherapy often become anaemic and may require blood transfusions. A large-scale audit of patients with a variety of solid tumours receiving chemotherapy at 28 specialist centers throughout the UK was undertaken to quantify the problem. Data were available from 2719 patients receiving 3206 courses of cytotoxic chemotherapy for tumours of the breast (878), ovary (856), lung (772) or testis (213). Their mean age was 55 years (range 16–87). Overall, 33% of patients required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
83
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 4 publications
5
83
0
Order By: Relevance
“…These findings indicate the important prognostic value of the pre-treatment Hb level for the risk of developing transfusion dependent anaemia, as reported by other investigators (Manegold, 1998;Groopman and Itri, 1999;Barrett-Lee et al, 2000). With the higher number of transfusions given, the potential side effects of RBC transfusions, such as viral infections, haemolysis, immunological or anaphylactic reactions may contribute to the risk associated with the treatment in this young patient population (Groopman and Itri, 1999;Mercadante et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings indicate the important prognostic value of the pre-treatment Hb level for the risk of developing transfusion dependent anaemia, as reported by other investigators (Manegold, 1998;Groopman and Itri, 1999;Barrett-Lee et al, 2000). With the higher number of transfusions given, the potential side effects of RBC transfusions, such as viral infections, haemolysis, immunological or anaphylactic reactions may contribute to the risk associated with the treatment in this young patient population (Groopman and Itri, 1999;Mercadante et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Another trial demonstrated a correlation between Hb levels during chemotherapy and response to therapy. This investigation has included patients with different types of solid tumours (Barrett-Lee et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chief aim of transfusion is to immediately correct the signs or symptoms resulting from anemia (Barrett-Lee et al, 2000). However, there is evidence in the literature that blood transfusion may have a negative impact on the progression of disease.…”
Section: Introductionmentioning
confidence: 99%
“…A low baseline Hb level has consistently been identified as a prominent factor associated with the likelihood of future transfusion [18][19][20][21][22][23][24][27][28][29][30]. A recent meta-analysis, which assessed the predictors of transfusion, pointed to the observation that prior RBC transfusion in cancer patients increases the risk for subsequent transfusions, with or without the use of epoetin alfa [31].…”
Section: Introductionmentioning
confidence: 99%